Supply chain optimization for electricity-based jet fuel: The case study Germany. (1st February 2022) - Wassermann, Timo; Muehlenbrock, Henry; Kenkel, Philipp; Zondervan, Edwin
Highlights: Novel power-to-liquid (PtL) supply chain optimization approach. In Germany, PtL production is favored in the greater North Sea coast area. To achieve 2 % PtL in aviation, an investment of 1.6 B€ is required for Germany. PtL production and supply costs range from 2052 to 2258 € t −1 . A PtL quota in aviation is recommended at national level and not as per airport. Abstract: Electricity-based jet fuel from renewables, also labeled sustainable aviation fuel (SAF), is expected to play a key role in the defossilization of aviation. The realization of first plants for the production of such power-to-liquid (PtL) fuels is imminent. This raises the challenge of an effective PtL supply chain design, which is addressed in this work. A novel optimization approach is introduced that enables an integrated selection of sites and technologies. Economically favorable supply chain designs are presented for the case study of Germany, with production primarily located in the wind power rich greater North Sea coast area. The Heide Refinery and Emsland Lingen Refinery sites are particularly suited for fuel synthesis, while cement and iron & steel plants are preferred as CO2 point sources. This study shows that at an electricity price of 0.05 € kWh −1, the costs for SAF production and supply range from 2052 to 2258 € t −1 . The minimum is obtained at a production volume equivalent to 4 % of the national jet fuel demand. To achieve the envisioned 2030 target of 2 % PtL SAF, an investment volume of 1.6 B€ is expected.